Intermediation in US and EU bond and swap markets: Stylised facts, trends and impact of the coronavirus (COVID-19) crisis in March 2020 - Martin Scheicher (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2023)
The trading of bonds and swaps largely relies on bank dealers as core market-makers. Dealers provide liquidity and trade the instruments with smaller or less active firms, in part by using their own balance sheets for inventory holding or hedging purposes. The reforms carried out in the aftermath of the global financial crisis (GFC) and the low interest rate environment have extensively changed the mechanisms and costs of trading fixed income instruments. This paper sets out to analyse the structure of trading in key over-the-counter (OTC) fixed income markets. We focus on three questions: (1) how are bonds and swaps currently traded and how liquid are these markets?, (2) how do the structural changes affect the dealer business model and market functioning?, and (3) how did the coronavirus (COVID-19) shock in March 2020 affect the OTC bond and swap market in its new post-reform set-up? To answer these questions, we combine an institutional and research perspective with a focus on key EU markets. We use public data and findings from the rich body of academic literature to describe the dealer business model and its post-GFC evolution. Overall, we argue that OTC fixed income trading is becoming "faster" due to the progress of electronic trading and the rise of non-bank traders, which has led bank dealers to make some adjustments to their market-making activities. The ongoing challenges faced in ensuring resilient provision of liquidity were also highlighted by the US bond market dislocation in March 2020.
Keywords: G12; G15; 330; Fixed income; market structure; liquidity; swaps; bonds; dealers